ACQUISITION OF BASIC PUBLIC SPEAKING SKILLS - Nataša Novaković; Boris Teodosijević (BizInfo)
With this texst we show that the acquisition of oratorical skills means not only mastering certain techniques of oratory, or public speaking, but that this is largely primarily related with a kind of mental preparation of speakers themselves, or in which way will future speakers access oratory as an art form or a skill, how will they experience oratory in their own understanding of this beautiful but demanding craft, craft that rewards us with different and great achievements in communication with our environment. Of course, provided that they are well prepared to master the art of public speaking. This preparation involves understanding and exploring the experiences of other well-known speakers, so that we get to know their own way to a magnificent oratory. Than it is necessary to set a clear goal to ourselves of what we want to achieve by studying these skills. Of course, our personal opinion, feeling and consciousness of public speaking must be positive and always strive for success. And above all, it is important to take every opportunity to exercise our public appearances and public speaking because exercise makes perfect.